2019
DOI: 10.1371/journal.pone.0219014
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of disease resistance, growth potential, and photosynthesis in tomato (Solanum lycopersicum) by inoculation with an endophytic actinobacterium, Streptomyces thermocarboxydus strain BPSAC147

Abstract: Biotic stresses in plants have a significant impact on agricultural productivity. In the present study, in vivo experiments were conducted to determine the physiological responses of tomato ( Solanum lycopersicum L.) seedlings by inoculation with an endophytic actinobacterium, Streptomyces thermocarboxydus isolate BPSAC147 under greenhouse conditions. Further, photochemical quantum yield of photosystem II (PSII) (F v /F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 71 publications
(94 reference statements)
2
23
0
Order By: Relevance
“…Several questions regarding the association of endophytic microorganisms with host plants, however, are still unanswered, including how long do they reside in the host and do they have any impact on photosynthesis. It appears evident that microbes can augment biotic stress tolerance in plants through the PGPB process (Passari et al 2019). Indeed, PGPB are known to produce various enzymes including amylase, chitinase, cellulase, invertase, lipase, keratinase, peroxidase, pectinase, protease, phytase, and xylanase which transform the complex nutrients into simple mineral forms.…”
Section: Growth-promoting Potential Noted On Pathogeninoculated Tomatmentioning
confidence: 99%
See 1 more Smart Citation
“…Several questions regarding the association of endophytic microorganisms with host plants, however, are still unanswered, including how long do they reside in the host and do they have any impact on photosynthesis. It appears evident that microbes can augment biotic stress tolerance in plants through the PGPB process (Passari et al 2019). Indeed, PGPB are known to produce various enzymes including amylase, chitinase, cellulase, invertase, lipase, keratinase, peroxidase, pectinase, protease, phytase, and xylanase which transform the complex nutrients into simple mineral forms.…”
Section: Growth-promoting Potential Noted On Pathogeninoculated Tomatmentioning
confidence: 99%
“…These endophytes colonize plant parts without causing any adverse effects. On many hosts, they act as plant growth-promoting, and/or biocontrol agents by direct antagonism or via the host by triggering induced resistance (Constantin et al 2019;Passari et al 2019). For instance, endophytic bacteria namely, Bacillus mojavensis was shown able to promote growth of maize plants infected with Fusarium verticillioides (Kalai-Grami et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They are well-known as an important source of bioactive natural products [53,54]. A recent study by Passari et al (2019) demonstrated that inoculation of tomato plants with Streptomycesthermocarboxydus (Actinobacteria) had a positive effect on plant growth, conferred protection against plant pathogen as well as production of carotenoids, benzenoids and avonoids [55]. Our results show that distinct plant-protecting taxa as well as enriched diversity might accumulate at this potential entry point for pathogens.…”
Section: Discussionmentioning
confidence: 54%
“…These findings are accordance with the results obtained in the current study, where DPPH and ABTS scavenging activity in chickpea plants were assessed. Even though numerous in-vivo pot experiments studies have already been reported on the ability of endophytic Actinobacteria [ 52 ] or other bacteria [ 53 ] to promote growth in a variety of plants, only a few of these studies also assessed antioxidant potential. Recently, Wang et al [ 54 ], studied the effect of endophytic Streptomyces chartreusis WZS021 on two sugarcane varieties under stress conditions and found that this Actinobacterium improved the stress tolerance of the host plant by regulating antioxidant levels.…”
Section: Discussionmentioning
confidence: 99%